Leaf Abscission lnduced by Ethylene in Water-Stressed lntact Seedlings of Cleopatra Manda& Requires Previous Abscisic Acid Accumulation in Roots - Gómez-Cadenas, Aurelio; Tadeo, Francisco R.; Talón, Manuel; Primo-Millo, Eduardo (ASBP, 2020)
The involvement of abscisic acid (ABA) in the process of leaf abscission induced by 1 -aminocyclopropane-1 -carboxylic acid (ACC) transported from roots to shoots in Cleopatra mandarin (Citrus reshni Hort. ex Tan.) seedlings grown under water stress was studied using norflurazon (NF). Water stress induced both ABA (24-fold) and ACC (16-fold) accumulation in roots and arrested xylem flow. Leaf bulk ABA also increased (&fold), although leaf abscission did not occur. Shortly after rehydration, root ABA and ACC returned to their prestress levels, whereas sharp and transitory increases of ACC (1 7-fold) and ethylene (1 O-fold) in leaves and high percentages of abscission (up to 47%) were observed. NF suppressed the ABA and ACC accumulation induced by water stress in roots and the sharp increases of ACC and ethylene observed after rewatering in leaves. NF also reduced leaf abscission (7-1070). These results indicate that water stress induces root ABA accumulation and that this is required for the process of leaf abscission to occur. It was also shown that exogenous ABA increases ACC levels in roots but not in leaves. Collectively, the data suggest that ABA, the primary sensitive signal to water stress, modulates the levels of ethylene, which is the hormonal activator of leaf abscission. This assumption implies that root ACC levels are correlated with root ABA amounts in a dependent way, which eventually links water status to an adequate, protective response such as leaf abscission